Development of a Needs Assessment Tool to Guide Surgical Training. (October 2016) - Braun, Kelli; Stepleman, Lara; Swift, Steven
Abstract : BACKGROUND: Needs assessments are an effective process for addressing educational training gaps. Given the absence of a standardized one for Ob-Gyn surgical training, the new Ob-Gyn milestones, and an increase in simulation, we developed an assessment tool to align our curriculum with perceived resident and faculty needs; studies demonstrate these groups do not always agree on those needs. METHODS: Development of the needs assessment tool utilized a systematic multi-step process. Literature review and informal interviews with faculty generated an initial outline. Content areas included feedback, surgical preparation, intra-operative performance, simulation, and the Ob-Gyn milestones procedures for Obstetrics and Gynecology technical skills. The procedures were assessed for: 1) current satisfaction with training and 2) perceived helpfulness of simulation to improve procedure performance. The iterative item reduction and refinement process of the initial tool included receiving feedback from two Ob-Gyn experts and a psychometric expert with subsequent revisions. One faculty and one resident also completed the needs assessment survey to ensure item clarity. RESULTS: A final 50-item tool was developed. Two equivalent versions were written to capture faculty and resident perceptions. DISCUSSION: We describe the process of developing a needs assessment tool to guide a programs surgical training priorities; the tool will be utilized in academic year 2015, providing further evidence of tool validity. This process can be followed to address other educational gaps.